Synthesis, spectral, crystallographic, and computational investigation of a novel molecular hybrid 3-(1-((benzoyloxy)imino)ethyl)-2H-chromen-2-ones - Krishnan, Kannan Gokula; Thanikachalam, Venugopal (European Journal of Chemistry, 2021)
Synthesis of 3-(1-((benzoyloxy)imino)ethyl)-2H-chromen-2-ones (1-5) was accomplished and it was characterized experimentally using various analytical techniques. Computational studies have been carried out for all compounds 1-5 using B3LYP method with 6-311++G(d,p) basis set. The optimized structural features viz. bond lengths, bond angles, and dihedral angles are compared with their single-crystal X-ray diffraction results of compound 1 (Crystal data for C18H13NO4 (M = 307.29 g/mol): Monoclinic, space group P21/c (no. 14), a = 11.399(5) Å, b = 5.876(5) Å, c = 21.859(5) Å, β = 91.060(5)°, V = 1463.9(14) Å3, Z = 4, T = 293(2) K, μ(MoKα) = 0.100 mm-1, Dcalc = 1.394 g/cm3, 13555 reflections measured (3.58° ≤ 2Θ ≤ 56.98°), 3669 unique (Rint = 0.0235) which were used in all calculations. The final R1 was 0.0444 (>2sigma(I)) and wR2 was 0.1506 (all data)), which are in good conformity with each other. Normal modes of vibrational frequencies of compounds 1-5 acquired from density-functional theory (DFT) method coincided with the experimental ones. The 1H and 13C chemical shifts of compounds 1-5 have been calculated by GIAO method and the results have been compared with the experimental ones. The first-order hyperpolarizability and their related properties of the novel molecules 1-5 are calculated computationally. The other parameters like natural bond orbital, zero-point vibrational energy, EHOMO, ELUMO, heat capacity and entropy have also been discussed.